Neither one thing nor the other : compulsory competitive tendering and southburgh cleansing services - MacIntosh, Ian [Verfasser]; Broderick, John [Verfasser] (My University, 1996)
"The 1988 Local Government Act greatly extended compulsory competitive tendering within local authorities. This paper adds to our understanding of changes to local government work organisation since the introduction of CCT through a case study of 'Southburgh' cleansing section - one of the first cleansing departments in the UK to open its services out to tender. We also provide an ethnographic input into current sociological debates about work such as putative moves towards flexibility and post-Fordism. The study points up the indeterminate nature of many of the changes that have taken place at Southburgh and calls for more detailed studies in order to fill out our understanding of the impact of competitive pressures within local government." (author's abstract, IAB-Doku) ((en)) Im Rahmen einer Fallstudie wird die Privatisierung der kommunalen Reinigungsdienste in Grossbritannien untersucht. Insbesondere wird auf die Änderung der Arbeitsorganisation und der Arbeitsverhältnisse eingegangen. (IAB)
Keywords: G 2.1.1 Ökonomie / Märkte; S 6.2.3 Metallerzeugung und -bearbeitung, Maschinenbau, Montierberufe (inkl. fahrzeugtechnischer Berufe); G 2.3.1 Arbeitsteilung & -organisation; I 2.2.1 Westeuropa; Öffentliches Unternehmen; Privatisierung; Straßenreiniger; Reinigungsberuf; Abfallbeseitigung; Berufsproblem; Arbeitsorganisation; Arbeitsbedingungen; Quantitative Angaben; Großbritannien; 1988-1994